2019
DOI: 10.1039/c9ra06607a
|View full text |Cite
|
Sign up to set email alerts
|

Global metabolomic profiling of trastuzumab resistant gastric cancer cells reveals major metabolic pathways and metabolic signatures based on UHPLC-Q exactive-MS/MS

Abstract: Resistance mechanism exploration has become an urgent need owing to the widespread trastuzumab resistance in gastric cancer. In this study, UHPLC-Q exactive MS/MS was carried out to characterize the metabolic profiles of human gastric cancer cell lines NCI N87, MKN45 (trastuzumab-sensitive) and NCI N87/R, MKN45/R (trastuzumab-resistant), respectively. Metabolic signatures and different metabolites were identified using multivariate in combination with univariate analysis. Integrated pathway enrichment analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…In this study, we investigated the inhibitory effect of PP on apoptotic cell death in CCA cell lines. We found that PP is an effective Previous studies showed that S-acetyldihydrolipoamide is found in gastric cancer cells and is associated with trastuzumab response 22 . Methylselenopyruvate is an α-keto acid metabolite of methylselenocysteine which acts as a histone deacetylase 8 (HDAC8) inhibitor that can restore Bcl2 modifying factor (BMF) downregulation and thereby activate apoptosis in colon cancer cells 23 .…”
Section: Discussionmentioning
confidence: 60%
“…In this study, we investigated the inhibitory effect of PP on apoptotic cell death in CCA cell lines. We found that PP is an effective Previous studies showed that S-acetyldihydrolipoamide is found in gastric cancer cells and is associated with trastuzumab response 22 . Methylselenopyruvate is an α-keto acid metabolite of methylselenocysteine which acts as a histone deacetylase 8 (HDAC8) inhibitor that can restore Bcl2 modifying factor (BMF) downregulation and thereby activate apoptosis in colon cancer cells 23 .…”
Section: Discussionmentioning
confidence: 60%
“…The metabolites with VIP values >1.0 and Q value < 0.05 were considered to be statistically significant, whereas variables that were not significantly changed were discarded ( 32 , 33 ). The metabolites identified were mapped by MS/MS spectral similarity with score ≄0.8 based on an in-house database ( 34 ). In addition, the differential metabolites were mapped into their biochemical pathways through metabolic pathway enrichment and pathway analysis based on MetaboAnalyst 5.0 ( http://www.metaboanalyst.ca ), which uses the high-quality Kyoto Encyclopedia of Genes and Genomes metabolic pathways as the backend knowledge base ( 34 , 35 ), and a pathway with p < 0.05 was considered to be significant ( 36 ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the differential metabolites were mapped into their biochemical pathways through metabolic pathway enrichment and pathway analysis based on MetaboAnalyst 5.0 (http://www.metaboanalyst. ca), which uses the high-quality Kyoto Encyclopedia of Genes and Genomes metabolic pathways as the backend knowledge base (34,35), and a pathway with p < 0.05 was considered to be significant (36). All data analyses were conducted using SPSS 22.0 (IBM Corp., Armonk, NY, USA) or RStudio version 1.2.1335-2009-2019 (RStudio, Inc.) software.…”
Section: Statistical and Bioinformatics Analysismentioning
confidence: 99%
“…Intracellular metabolites extractions were performed according to methods that were utilized in our previous study 14 . Briefly, cells were seeded in 6-well plates for 48-72 h in complete medium after which cells were harvested and counted at a density of 1×10 7 cells/well.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent data processing and analysis was accomplished using the bioinformatics program XCMS in R package (version 3.3.0) 15 . The parameters settings were accomplished as it was in our previous study 14 . OSI-SMMS software (version 1.0, Dalian Chem Data Solution Information Technology Co. Ltd.) was further used for peak annotation after XCMS data.…”
Section: Methodsmentioning
confidence: 99%